The past and present of Japanese immigration to Mexico: towards a future agenda for the study of the Japanese immigrant community in Guanajuato - Vila Freyer, Ana (Acta Universitaria, 2017)
Since 2011, Guanajuato has become Mexico’s main destination of immigrants of Japanese origin, leading to a North-South migration phenomenon, a novelty in a state that used to be seen as a traditional expeller of the population. Guanajuato has also been the main attractor for Japanese investment, especially in the automotive sector. Japanese capital has instigated an intense process of formation of specific community formation in the State, particularly of corporate expatriates from automotive corporations, who are based in the main cities in Guanajuato. From the few studies of a similar phenomenon in Monterrey and Guadalajara, this document highlights the importance of starting a research agenda to follow the creation of these new communities in the State.
Keywords: Array; Array; Array; Array